Examining Micro-Level Homicide Patterns in Toronto, 1967 Through 2003 - Harinam, Vincent (Canadian journal of criminology and criminal justice, 2020)
This article assesses the spatial distribution and developmental pattern of micro-level homicide clusters in Toronto between 1967 and 2003. The spatial unit of analysis is the street segment and is defined as the two block faces on both sides of a street between two intersections. Three time periods (1967 to 1979, 1980 to 1989, and 1990 to 2003) covering 1,671 homicides were pooled to ensure sufficient numbers for analysis. Given the qualitative strength of the dataset, a series of descriptive statistics and geospatial statistics are used. Toronto's developmental homicide pattern is characterized by a dense concentration of single-homicide street segments within the downtown core between 1967 and 1989, with the mass dispersal of multi-homicide street segments across the city between 1990 and 2003. Single-homicide street segments accounted for 84% and 81% of homicides between 1967 and 1979 and 1980 and 1989, respectively. However, multi-homicide street segments tripled between 1990 and 2003, rising from 16% of homicides in the first time period to 45% in the third. Th is reflects a change in the character of homicides with drug and gang-related homicides increasing in the third time period. (English)